An Investigation on Financial Development, Trade Openness and Economic Growth: Var Approach - HASAN, HAFNIDA; ALI, BASEL J. A.; JOSEPH, NYMPHA; OUDAT, MOHAMMAD SALEM (The journal of contemporary issues in business and government, 2021)
The aim of this analysis is to examine the impact on economic growth in Bahrain from 1986 to 2018 from FDs and trade openness. To investigate the data, the Vector Autoregressive Model (VAR) and the causality of Granger have been used. The results show that all vector lives are co-integrated at 5 percent meaningful levels in the long term. In the near term, economic growth will only be influenced by financial progress. The Granger Causality (CC) Test reveals the unidirectionality of global and financial developments. In this way, policymakers should advance FD and promote more free markets, in the end the aim is to increase economic growth.